Hormones, subjective night and season of the year - Illnerová, H; Sumová, A; Trávnícková, Z; Jác, M; Jelínková, D (Physiological research, 2000)
Production and release of many mammalian hormones exhibit circadian rhythms controlled by a pacemaker located in the suprachiasmatic nuclei (SCN) of the hypothalamus. Under conditions when the circadian pacemaker free-runs with a period close to, but not equal to 24 h, subjective day and night may not be identical with the environmental day and night. The present study was aimed to define the phase and state of the circadian pacemaker when the circadian system is experiencing subjective night and to ascertain whether and how such a defined subjective night depends on the photoperiod. The results indicate that the subjective night may be defined as the time interval when i) light stimuli can reset the circadian system, ii) pineal melatonin production and photic induction of the c-Fos gene in the ventrolateral SCN are high, and iii) the spontaneous c-Fos protein production in the dorsomedial SCN is low. Such a defined subjective night and, logically, the whole circadian pacemaking system depend on the photoperiod and hence on the season of the year which the animals are experiencing.
Keywords: cirkadiánní rytmus; Humans; protoonkogenní proteiny c-fos; světlo; regulace genové exprese; melatonin; hormony; fotoperioda; lidé; zvířata; Hormones; Light; Darkness; Circadian Rhythm; roční období; Gene Expression Regulation; nucleus suprachiasmaticus; Seasons; Photoperiod; Animals; Proto-Oncogene Proteins c-fos; tma; Suprachiasmatic Nucleus; Melatonin